Lack of interleukin-6/glycoprotein 130/signal transducers and activators of transcription-3 signaling in hepatocytes predisposes to liver steatosis and injury in mice - Kroy, Daniela Christina; Beraza, Naiara; Tschaharganeh, Darjus-Felix; Sander, Leif Erik; Erschfeld, Stephanie; Giebeler, Arne; Liedtke, Christian; Wasmuth, Hermann Elard; Trautwein, Christian; Streetz, Konrad (Hepatology, 2010)
A deregulated cytokine balance is involved in triggering the sequence from steatosis to nonalcoholic steatohepatitis, ultimately leading to liver fibrosis and cancer. To better define the role of proinflammatory interleukin-6 (IL-6)-type cytokines in hepatocytes we investigated the role of IL-6 and its shared receptor, glycoprotein 130 (gp130), in a mouse model of steatohepatitis. IL-6−/− mice were fed a choline-deficient, ethionine-supplemented (CDE) diet. Conditional gp130 knockout and knockin mice were used to achieve hepatocyte-specific deletion of gp130 (gp130Δhepa), gp130-dependent rat sarcoma (Ras)-(gp130ΔhepaRas), and signal transducers and activators of transcription (STAT)-(gp130ΔhepaSTAT) activation. CDE-treated IL-6−/− mice showed a significant hepatic steatosis at 2 weeks after feeding. The mice rapidly developed elevated fasting blood glucose, insulin serum levels, and transaminases. To better define IL-6-dependent intracellular pathways, specifically in hepatocytes, we next treated gp130Δhepa mice with a CDE diet. These animals also developed a marked steatosis with hyperglycemia and displayed elevated insulin serum levels. Additionally, gp130Δhepa animals showed an imbalanced inflammatory response with increased hepatic tumor necrosis factor-alpha and decreased adiponectin messenger RNA levels. Dissecting the hepatocyte-specific gp130-dependent pathways revealed a similar disease phenotype in gp130ΔhepaSTAT mice, whereas gp130ΔhepaRas animals were protected. In CDE-treated mice lack of gp130-STAT3 signaling was associated with immune-cell-infiltration, jun kinase-activation, a blunted acute-phase-response, and elevated transaminases. Furthermore, gp130Δhepa and gp130ΔhepaSTAT mice showed beginning signs of liver fibrosis compared to gp130ΔhepaRas mice and controls. Conclusion:During CDE treatment mice lacking IL-6 and gp130-STAT signaling in hepatocytes are prone to hepatic metabolic changes and inflammation. This ultimately leads to progressive steatohepatitis with signs of liver remodeling. Thus, the presented model allows one to further dissect the role of IL-6/gp130-type signaling in hepatocytes during fatty liver degeneration to define new therapeutic targets in metabolic liver diseases. (HEPATOLOGY 2010.)
Gesehen am 06.03.2023